THE POSSIBILITY OF EARLY PREDICTION OF INFLAMMATORY COMPLICATIONS IN PATIENTS OPERATED ON THE ACUTE INTRA-ABDOMINAL - Прихідько, Р.А.; Шейко, В.Д.; Ситнік, Д.А. (World of Medicine and Biology, 2014)
The article highlights the urgent problems of prediction and prevention of postoperative inflammatory complications in patients operated on the acute intra-abdominal pathology. The possibilities of different forecasting systems of these complications and possible ways to prevent them. The literature suggests the possibility of predicting inflammatory complications in various pathological conditions and diseases, but reviewed the literature and found no reliable systems for assessment of the risk for acute intraabdominal pathology. Despite the large number of published data, the issue of prevention of postoperative inflammatory complications in patients with acute intra-abdominal pathology is no clear algorithm that takes into account the risk of their development, and encourages it to further study the issue.